Annual Plan 1990-91 Government of Bihar - Planning Commission (Planning Commission, 1990)
Growth of State Domestic Product and Per Capita Income. 1.1.1. the rate of growth of the State Domestic Product (S.D.P.) of Bihar has shown a significant increase during the eighties. Even if we ignore the high growth rate of 10.48 per cent in 1980-81 over the previous year 1979-80 which happened to be a year of severe drought with a low agricultural production base and adopt the average for the triennial ending 1980-81 as the base, the S.D.P. during the Sixth Five-year Plan (1980-85) grew at the rate of 4.05 per cent per annual compound at 1970-71 prices. the growth rate during the first four years of the Seventh Plan works out to 4.39 per cent per annum compound.
Planning Department